Transformation optics with low-loss plasmonic circuitry - Ng, Seng Guan (Nanyang Technological University, 2021)
Design a wave adaptor with nanostructured dielectric materials using transformation optics to reduce the effect of scattering and power loss when surface plasmon wave propagates along an uneven surface. The material that will be used for designing of the wave adaptor will be of minimal attenuation coefficient which will introduce minimal loss while reducing the scattering. In achieving this, it will help in reducing the total loss of the standalone device used in optical circuits.